Compassionate Nitric Oxide Adjuvant Treatment of Persistent Mycobacterium Infection in Cystic Fibrosis Patients. Issue 4 (April 2018) - Yaacoby-Bianu, Karin; Gur, Michal; Toukan, Yazeed; Nir, Vered; Hakim, Fahed; Geffen, Yuval; Bentur, Lea
Abstract : Background: Mycobacterium abscessus is one of the most antibiotic-resistant pathogens in cystic fibrosis (CF) patients. Nitric oxide (NO) has broad-spectrum antimicrobial activity. Clinical studies indicated that it is safe and tolerable when given as 160 ppm intermittent inhalations. Methods: A prospective compassionate adjunctive inhaled NO therapy in 2 CF patients with persistent Mycobacterium abscessus infection. Results: No adverse events were reported. Both subjects showed significant reduction in quantitative polymerase chain reaction results for Mycobacterium abscessus load in sputum during treatment; estimated colony forming unit decreased from 7000 to 550 and from 3000 to 0 for patient 1 and patient 2, respectively. Conclusions: Intermittent inhalations with 160 ppm NO are well tolerated, safe and result in significant reduction of Mycobacterium abscessus load. It may constitute an adjuvant therapeutic approach for CF patients with Mycobacterium abscessus lung disease. Further studies are needed to define dosing, duration and long-term clinical outcome.